Optimizing Power Flow: A Study of Newton Raphson (NR) Method for Load Flow Analysis (LFA) in Power Systems - Raza, Ali; Zahid, Tausif; Iqbal, Shahid; Ahmad, Ishfaq; Hussain, Jawad (Innovative Computing Review, 2024)
This paper considers the application of an iterative method, namely the Newton Raphson (NR) method, for the study of load flow analysis (LFA) in power systems. The NR method is employed due to its computational efficiency and the ability to handle nonlinear equations. The primary objectives of LFA are to determine the specified active power (SAP), specified reactive power (SRP), active power injection (API) from and to bus, reactive power injection (RPI) from and to bus, active power loss (APL), reactive power loss (RPL), and voltage magnitude (|V|) at each node of the distribution network (DN). This technique is assessed through MATLAB simulations carried out on the IEEE-33 and IEEE-69 bus DNs.